ANALISIS KAPASITAS DAN OPTIMALISASI APRON TERMINAL I BANDAR UDARA INTERNASIONAL SOEKARNO-HATTA - , TAQIA RAHMAN; , Ir. H. Wardhani Sartono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Soekarno-Hatta International Airport is a collector or hub airport in one of the 12 airports managed by PT. Angkasa Pura II. Airports Council International (ACI) in Switzerland launched the statistical results of the busiest airport in the world (busiest Airport in the World) in 2012, and put the Soekarno-Hatta International Airport (CGK) at number 9th with 57.772.762 passengers movement in 2012, with a growth rate of 12, 1%. Increased growth of air transport in Indonesia is in contrast to the condition of the air transport infrastructure in Indonesia. Based on the report of the WEF Global Competitiveness Report 2011-2012, infrastructure conditions and Indonesia ranked 80th among the air transport infrastructure around the world. It is a challenge for airports in Indonesia to develop its infrastructure. One of the Infrastructures is apron, which is an area that consists of a parking space plane (aircraft parking position) and gates for passengers up and down the plane. This study aims to analyze the capacity and needs of parking stands in Apron Terminal 1 Soekarno-Hatta International Airport (domestic flights) in the existing condition and the conditions of 5 and 10 years, namely in 2017 and 2022. The research is conducted by analyzing historical pattern of movement of passengers data in Terminal 1 for 12 years (2001-2012) which is owned by PT. Angkasa Pura II (Persero) by using the method of forecasting time-series (extrapolating the linear regression). The forecasting results converted to the movement of passengers at peak hours using Pignataro method based on the characteristics of the peak hour Soekarno-Hatta Airport in 2012. Aircraft movements at the peak in 2017 and 2022 obtained by converting the movement of passengers based on the characteristics of each aircraft at Terminal Apron. The results showed that in 2017 and 2022 (5 and 10 years from now), Terminal 1 Apron capacity was exceeded (volume capacity ratio greater than 1) and can no longer accommodate the movement of aircraft at peak hours so it needs the action of optimizing. Based on this research, parking stands needs of Apron Terminal 1 in 2017 is 10 parking stands, whereas in 2022 needs 22 parking stands. The Apron Terminal 1 optimization plan for conditions 5 and 10 years is to expand in the area of development apron International Airport Soekarno-Hatta.